A modelling study and optimization of catalytic reduction of NO over CeO2-MnOx (0.25)-Ba mixed oxide catalyst using design of experiments - Mousavi, Seyed Mahdi (Environmental technology, 2014)
In this study, the effects of operation variables on catalytic performance of CeO2-MnOx (0.25)-Ba mixed oxide in catalytic reduction of NO with ammonia are investigated by using design of experiments. A response surface methodology (RSM) combined with the central composite design (CCD) is used to model and optimize the process variables, including concentration of 02 (vol.%), NH3/NO ratio in the gas feed, gas hourly space velocity (GHSV) and reaction temperature (degrees C) on the NO conversion and N2 selectivity as responses. The R2 values for both generated models were greater than 0.9, confirming the capability of quadratic RSM model in fitting the obtained experimental data. According to the results, GHSV had the largest and negative effect on the NO conversion, while it was an insignificant parameter on the N2 selectivity in the design space. Also, NH3/NO ratio was the most effective parameter on the N2 selectivity. Under the optimum conditions: 4.75 vol.% O2, NH3/NO ratio of 0.9, GHSV of 12,000 h(-1) and 197.5 degrees C, the predicted values for NO conversion and N2 selectivity were 96.47% and 93.96%, respectively. The obtained experimental values in optimum condition agreed with those predicted, indicating suitability of the RSM model to estimate the values of the responses